Spinal cord ability ruler: an interval scale to measure volitional performance after spinal cord injury - Reed, R.; Rupp, Rüdiger; Weidner, Norbert (Spinal cord, 2017)
Study design:Retrospective statistical analysis of database.Objective:Spinal cord injury (SCI) clinical trials are challenged to enroll participants, and early trial outcomes have often been equivocal. We hypothesized that a specifically designed novel true linear interval-scaled outcome measure targeted to simultaneously track a broad range of SCI will enable more inclusive enrollment of participants and valid comparisons of functional changes after SCI.Methods:To define a single SCI measurement framework, we used items from existing measures. To evaluate linearity and validity of the measure, we used rigorous psychometric Rasch analysis on two data sets from over 2500 traumatic SCI participants (all levels and severities of SCI) within the EMSCI (European Multicenter study about SCI) database.Results:Volitional performance was found to be the unidimensional construct that would detect and track a treatment effect from a central nervous system-directed therapeutic. Along with early evidence for voluntary neurological control of upper-extremity muscle contractions, volitional performance is best described by goal-directed activities of daily living that are increasingly difficult to re-acquire when activity within more caudal spinal segments is required. Validity of the Spinal Cord Ability Ruler (SCAR) as a linear interval construct was confirmed with Rasch analysis. All measurement items were properly ordered, as well as being precise and stable across clinically relevant groups. Only 5/24 items had some misfit. Targeting was excellent over time after SCI, with few gaps and only modest floor and ceiling effects (3% each).Conclusions:SCAR is a quantitative linear measure of volitional performance across an inclusive range of tetraplegic and paraplegic SCI.
Gesehen am 24.04.2018